Rock slope stability analysis by approximation of geological strength index and finite element method - Agus Nugroho Soewignjo; Yusa Muhamad; Ongko Andarsin (MATEC Web of Conferences, 2019)
As a part of natural geography systems, rock slopes have treasured amount of natural resources potential. The rock materials could be utilized to fulfill several needs, especially to construct buildings. However, society sometimes have taken advantages from the slope’s existence in wrong ways. The exploitations toward rock materials, either through manual or modern way (blasting) have caused some cracks occurred. These cracks have reduced the stability of rock slopes and easily triggered failures on rock slopes. In this paper, the stability of a rock slope will be precisely discussed by using Geological Strength Index (GSI) and was analyzed by using finite element method. The rock samples were taken from Pangkalan (West Sumatera, Indonesia), which this location is also vulnerable to rock slope failures. Geological Strength Index was obtained by doing manual observations on rock sample’s properties, i.e. joint, cracks, and discontinuity. The result was consisted of rock’s properties. Meanwhile, the analysis by using finite element method produced an outcome in form of safety factor. This result could be made as a reference for pre-disaster mitigation in Pangkalan.